Alterations of human placental epidermal growth factor receptor in intrauterine growth retardation. - Fondacci, C (1994)
We studied human placental microvillous EGF receptor (EGFR) and its relationship with maternal and placental features in 14 cases of intrauterine growth retardation. Placental EGFR phosphorylation was significantly decreased or absent in 12 cases of small for gestational age neonates, as shown by SDS-PAGE, autoradiography, and scanning analysis. Specific [125I]EGF binding and Scatchard plots of the binding data showed a decreased number of EGFR in 6 of the 12 cases, with a mean maximal binding capacity of 1.09 +/- 0.32 pmol/mg for high affinity sites (mean control value = 2.30 +/- 0.23 pmol/mg). Most of the hypertensive women and smokers belonged to this subgroup. In three of the remaining six cases of small gestational age placentas with low EGFR phosphorylation, there was no maternal pathology or significant parenchymatous placental lesions. Five showed a 175-kD EGFR species when probed by [125I]EGF cross-linking and Western blotting with RK2 and C-Term, two polyclonal anti-EGFR antibodies, suggesting abnormal transduction of the EGF-induced signal. The sixth placenta yielded a single 145-kD EGFR band consistent with an abnormal EGFR structure; Western blot analysis showed no immunoreactive band. In conclusion, maternal and placental pathologies in intrauterine growth retardation are associated with various alterations of placental EGFR, pointing out the importance of EGFR ligands in the regulatory pathway of placental and fetal growth.